2021
DOI: 10.3390/biomedicines10010060
|View full text |Cite
|
Sign up to set email alerts
|

COX5B-Mediated Bioenergetic Alterations Modulate Cell Growth and Anticancer Drug Susceptibility by Orchestrating Claudin-2 Expression in Colorectal Cancers

Abstract: Oxidative phosphorylation (OXPHOS) consists of four enzyme complexes and ATP synthase, and is crucial for maintaining physiological tissue and cell growth by supporting the main bioenergy pool. Cytochrome c oxidase (COX) has been implicated as a primary regulatory site of OXPHOS. Recently, COX subunit 5B (COX5B) emerged as a potential biomarker associated with unfavorable prognosis by modulating cell behaviors in specific cancer types. However, its molecular mechanism remains unclear, particularly in colorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Our results agreed with previously published literature on the impact of its high expression on tumor invasiveness and poor prognosis in patients with breast cancer [43]. More recently, further insights have confirmed its tremendous role as a growth-promoting gene, both in hepatoma [44] and colorectal cancer [45]. Interestingly, the combined upregulation of COX5B and ATP5H was also reported by Yusenko et al in renal oncocytomas [19].…”
Section: Discussionsupporting
confidence: 93%
“…Our results agreed with previously published literature on the impact of its high expression on tumor invasiveness and poor prognosis in patients with breast cancer [43]. More recently, further insights have confirmed its tremendous role as a growth-promoting gene, both in hepatoma [44] and colorectal cancer [45]. Interestingly, the combined upregulation of COX5B and ATP5H was also reported by Yusenko et al in renal oncocytomas [19].…”
Section: Discussionsupporting
confidence: 93%
“…Mitochondria play a predominant role in regulating energy metabolism, ATP production and oxygen consumption and for the maintenance of cellular functions (Chu et al. 2021 ). The increased OCR is an important indicator, which reflects the mitochondrial respiratory chain complex activity (du Plessis et al.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al also reported that COX6C is a negative prognostic biomarker in MM [ 46 ]. Similar to COX6C, COX5B was found to promote cell growth and reduce anticancer drug susceptibility in colorectal cancer cells, which may lead to unfavorable postoperative outcomes for patients with colorectal cancer [ 47 ]. Bioenergetic alteration-dependent activation of AMPK was found to occur in hepatoma cells via COX5B regulation of UHMK1 expression [ 48 ].…”
Section: Discussionmentioning
confidence: 99%